Assessment of serum carcinoembryonic antigen in colorectal cancer patients treated by surgery and chemotherapy - Shahbaa A. Al-Bayati (University of Mosul, 2011)
Objective: Carcinoembryonic antigen (CEA) is a protein found in many types of cells associated with tumors and the developing fetus. The main use of CEA is as a tumor marker, especially with intestinal cancer. This study was designed to evaluate the effect of surgery and chemotherapy on the level of CEA. Patients and methods: The study was carried out in Al-Jamhoory Teaching Hospital in Mosul from January to July 2010. Thirty patients with colorectal carcinoma were treated by surgical removal of the cancer and chemotherapy. Blood samples were taken from the patients one week before surgery and other blood samples were taken one week after surgery. Third blood samples were taken after one week of the first cycle of chemotherapy. Serum carcinoembryonic antigen, ALP (alkaline phosphatase), ALT (alanine aminotransferase), total serum bilirubin (TSB), and albumin were estimated from the samples. Results: After surgery serum CEA and WBCs were decreased significantly (P < 0.001). Serum ALP was also decreased significantly (P < 0.05), while serum ALT, TSB, and albumin were not changed significantly after surgery compared with the results before surgery. After chemotherapy, serum CEA and WBCs decreased significantly (P < 0.001) compared with the results after surgery. At the same time, serum ALP, ALT, TSB, and albumin did not change significantly after chemotherapy. Conclusion: Surgical removal of tumor decreased CEA level, but it did not normalize. Serum CEA can be used as a marker for the effectiveness of the chemotherapy on colorectal cancer.